Depressive symptoms prior to and following insulin initiation in patients with type 2 diabetes mellitus: Prevalence, risk factors and effect on physician resource utilisation. Issue 5 (October 2015) - Dzida, Grzegorz; Karnieli, Eddy; Svendsen, Anne Louise; Sølje, Kristine Steensen; Hermanns, Norbert; ,
Highlights: We evaluated depressive symptoms in T2DM patients initiating insulin. Depressive symptoms improved despite initiation of basal insulin therapy. Depressive symptoms were associated with increased healthcare resource utilisation. Abstract: Aims: To study the frequency and intensity of depressive symptoms and associations with physician resource utilisation following insulin initiation in patients with type 2 diabetes mellitus. Methods: SOLVE was a 24-week observational study. In this sub-analysis of data from Poland, depressive symptoms were evaluated using the Patient Health Questionnaire (PHQ)-9. Results: PHQ-9 was completed by 942 of 1169 patients (80.6%) at baseline, and 751 (64.2%) at both baseline and final (24-week) visit. PHQ-9 scores indicated depressive symptoms in 45.6% ( n  = 430) at baseline, and 27.2% ( n  = 223) at final visit. Mean PHQ-9 change was −2.38 [95% CI −2.73, −2.02], p  < 0.001. Depressive symptoms at baseline (OR 6.32, p  < 0.001), microvascular disease (OR 2.45, p  = 0.016), number of physician contacts (OR 1.16, p  = 0.009), and change in HbA1c (OR 0.60, p  = 0.025) were independently associated with moderate/severe depressive symptoms at final visit. Patients with more severe depressive symptoms spent more time training to self-inject ( p  = 0.0016), self-adjust ( p  = 0.0023) and manage other aspects of insulin delivery ( p  < 0.0001). Patients with persistent depressive symptoms had more telephone contacts and dose changes at final visit than those without (both p  < 0.05). Conclusions: Depressive symptoms are common with type 2 diabetes and associated with increased healthcare utilisation, reinforcing the need for holistic interdisciplinary management approaches.